1991
DOI: 10.1111/j.1365-2133.1991.tb06041.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the menstrual cycle and pregnancy on atopic dermatitis

Abstract: The prevalence of a premenstrual deterioration in the symptoms of atopic dermatitis, as determined by a postal questionnaire completed by 150 women, was 33%. There was a significant association between a premenstrual worsening of atopic dermatitis and the presence of the symptoms of the premenstrual syndrome (P less than 0.002). Pregnancy had an adverse effect on atopic dermatitis in the majority of cases (52%), usually starting in the first 20 weeks of gestation, although an appreciable proportion of women (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 15 publications
3
56
0
2
Order By: Relevance
“…Cho et al, in a similar interview-based study in Korea found symptoms improvement in 4% while 61% experienced deteriorations [36]. Kemmett et al, documented deteriorations in 52%, improvement in 24% and stable disease in 24% [37]. Similar deterioration in the presence of premenstrual syndrome (PMS) was noted in 46% of women menstruating suggesting an existing relationship between pregnancy hormones and fluctuation of eczema in pregnancy [36,37].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cho et al, in a similar interview-based study in Korea found symptoms improvement in 4% while 61% experienced deteriorations [36]. Kemmett et al, documented deteriorations in 52%, improvement in 24% and stable disease in 24% [37]. Similar deterioration in the presence of premenstrual syndrome (PMS) was noted in 46% of women menstruating suggesting an existing relationship between pregnancy hormones and fluctuation of eczema in pregnancy [36,37].…”
Section: Discussionmentioning
confidence: 94%
“…Kemmett et al, documented deteriorations in 52%, improvement in 24% and stable disease in 24% [37]. Similar deterioration in the presence of premenstrual syndrome (PMS) was noted in 46% of women menstruating suggesting an existing relationship between pregnancy hormones and fluctuation of eczema in pregnancy [36,37]. However, the fact that psychological symptoms of PMS could increase awareness of cutaneous symptoms and failure of hormone replacement treatment suggest further studies are needed for better understanding of the role hormones.…”
Section: Discussionmentioning
confidence: 95%
“…Atopic dermatitis is more likely to deteriorate than to remit in pregnancy. 23 In some countries, especially Sweden and Chile-Bolivia, ICP patients constitute a fairly large patient group. We suggest that pregnant women with pruritus should be surveilled with repeated determinations of serum bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy may also aggravate the symptoms in some patients, while in others an improvement may be seen. These observations strongly suggest that hormonal changes also have an influence on atopic eczema (38).…”
Section: Diagnosis and Avoidance Of Environmental Provocation Factorsmentioning
confidence: 73%